NIR‐Assisted MgO‐Based Polydopamine Nanoparticles for Targeted Treatment of Parkinson's Disease through the Blood–Brain Barrier (Adv. Healthcare Mater. 23/2022). Issue 23 (8th December 2022) - Gao, Yifei; Cheng, Yuxue; Chen, Jiapeng; Lin, Danmin; Liu, Chao; Zhang, Ling‐Kun; Yin, Liang; Yang, Runcai; Guan, Yan‐Qing
Abstract : Parkinson's Disease In article 2201655, Yan‐Qing Guan and co‐workers successfully develop a novel photo‐controlled drug delivery system for the treatment of Parkinson's disease. This nanoparticle uses MgO nanoparticles as a substrate, polydopamine as a shell and carries anti‐SNCA plasmid and puerarin. Under the irradiation of 808 nm near‐infrared light, the composite nanoparticles in deep tissues are activated, then absorbed by nerve cells after penetrating the blood–brain barrier, playing the role of antioxidation, anti‐inflammation and inhibiting the accumulation of α‐synuclein. Therefore, this strategy for intracerebral drug delivery can be an ideal approach to combat neurodegenerative diseases.